Management of benign oesophageal strictures: our experience at tertiary care centre - Varudkar, Anagha S.; Deshmukh, Santoshkumar N.; Vitekar, Dyanesh D. (International Surgery Journal, 2017)
Background: Oesophageal stricture is a common problem in general surgical practice. It can be benign or malignant, simple or complex. Benign oesophageal strictures include peptic, corrosive, post-surgical anastomotic strictures, post radiotherapy and drug induced strictures. The aetiology of this condition varies in developed and developing countries. Aim of present study was to determine the aetiology of benign oesophageal stricture, to evaluate the role of endoscopic dilatation of stricture and final outcome in these patients in our region. Methods: This prospective descriptive study was conducted in department of surgery at a tertiary care teaching hospital at Aurangabad from December 2009 to November 2013. All the patients, regardless of age and gender, admitted with diagnosis of benign oesophageal stricture were included in the study. Depending upon the type of stricture treatment was carried out. Postoperatively patients were followed up for detection of possible complications and their treatment. Results: Total 50 patients of oesophageal stricture were studied. Mean age was 33.65 years with male to female ratio 2.8:1. Ingestion of corrosive substance was the commonest etiology noted followed by peptic strictures. Conclusions: Corrosive ingestion was the commonest cause of benign oesophageal stricture in our region followed by peptic strictures. Endoscopic dilatation is safe and effective in treating benign oesophageal strictures.